Membrane distillation for achieving high water recovery for potable water reuse. (February 2022) - Ngo, My Thi Tra; Diep, Binh Quoc; Sano, Hideaki; Nishimura, Yasuhisa; Boivin, Sandrine; Kodamatani, Hitoshi; Takeuchi, Haruka; Sakti, Satya Candra Wibawa; Fujioka, Takahiro
Abstract: Achieving high water recovery using reverse osmosis membranes is challenging during water recycling because the increased concentrations of organics and inorganics in wastewater can cause rapid membrane fouling, necessitating frequent cleaning using chemical agents. This study evaluated the potential of membrane distillation to purify reverse osmosis-concentrated wastewater and achieve 98% overall water recovery for potable water reuse. The results indicate that membrane fouling during membrane distillation treatment was low (4% reduction in permeability) until 98% water recovery. In contrast, membrane fouling during reverse osmosis treatments was high (73% reduction in permeability) before reaching 90% water recovery. Furthermore, membrane distillation showed superior performance in removing dissolved ions (99.9%) from wastewater as compared with reverse osmosis (98.9%). However, although membrane distillation removed most trace organic chemicals tested in this study, a negligible rejection (11%) was observed for N -nitrosodimethylamine, a disinfection byproduct regulated in potable water reuse. In contrast, RO treatment exhibited a high removal of N -nitrosodimethylamine (70%). Post-treatment (e.g., advanced oxidation) after reverse osmosis and membrane distillation may be needed to comply with the N -nitrosodimethylamine regulations. Overall, the membrane distillation process had the capacity to purify reverse osmosis concentrate with insignificant membrane fouling. Graphical abstract: Image 1 Highlights: Treating RO concentrates with MD could increase water recovery to 98%. MD reversed minor membrane fouling, resulting in a 4% flux reduction. MD exhibited a higher conductivity removal (99.9%) than RO (98.9%). The two processes had comparable removal of trace organic chemicals. However, MD exhibited a low NDMA removal (11%) compared with RO (70%).